Characterization of Soil Actinomycetes From Malino Pine Forest Rhizosphere of South Sulawesi - Eka Sukmawaty; Sitti Rahmah Sari; Mashuri Masri (Elkawnie, 2020)
Abstract: Actinomycetes are a group of Gram-positive bacteria that produce active compounds with a wide distribution range in nature especially in soil. The purpose of this study was to isolate actinomycetes from the rhizosphere soil of the Malino pine forest, South Sulawesi. This research is a descriptive qualitative study of 15 actinomycetes isolated from the rhizosphere soil of the Pine Forest. These 15 isolates have been successfully identified to the genus level. Actinomycetes were isolated by direct dilution method and further morphological identification was carried out. Actinomycetes were isolated on yeast malt agar (YMA) medium. The growing isolates showed colony colors brown, gray, and white. Produces yellow, brown, and beige color pigments. Based on the characterization carried out, all isolates were identified into the genus Streptomyces.Abstrak: Aktinomisetes merupakan kelompok bakteri gram positif yang menghasilkan senyawa aktif dengan rentang distribusi yang luas di alam, terutama di tanah. Tujuan penelitian ini untuk mengisolasi aktinomisetes dari tanah rizosfer hutan pinus Malino Sulawesi Selatan. Penelitian ini merupakan penelitian kualitatif deskiptif terhadap 15 isolat aktinomisetes yang diisolasi dari tanah rizosfer Hutan Pinus Malino Sulawesi Selatan. 15 isolat ini telah berhasil didentifikasi sampai tingkat genus. Aktinomisetes diisolasi dengan metode pengenceran secara langsung dan dilakukan identifikasi morfologi lebih lanjut. Aktinomisetes diisolasi pada media yeast malt agar (YMA). Isolat yang tumbuh memperlihatkan warna koloni coklat, abu-abu dan putih. Menghasilkan pigmen warna kuning, coklat dan krem. Berdasarkan karakterisasi yang dilakukan keseluruhan isolat teridentifikasi ke dalam genus Streptomyces.